Optimizing a spontaneously contracting heart tissue patch with rat neonatal cardiac cells on fibrin gel. (28th April 2014) - Tao, Ze‐Wei; Mohamed, Mohamed; Hogan, Matthew; Gutierrez, Laura; Birla, Ravi K.
Abstract: Engineered cardiac tissues have been constructed with primary or stem cell‐derived cardiac cells on natural or synthetic scaffolds. They represent a tremendous potential for the treatment of injured areas through the addition of tensional support and delivery of sufficient cells. In this study, 1–6 million (M) neonatal cardiac cells were seeded on fibrin gels to fabricate cardiac tissue patches, and the effects of culture time and cell density on spontaneous contraction rates, twitch forces and paced response frequencies were measured. Electrocardiograms and signal volume index of connexin 43 were also analysed. Patches of 1–6 M cell densities exhibited maximal contraction rates in the range 305–410 beats/min (bpm) within the first 4 days after plating; low cell density (1–3 M) patches sustained rhythmic contraction longer than high cell density patches (4–6 M). Patches with 1–6 M cell densities generated contractile forces in the range 2.245–14.065 mN/mm 3 on days 4–6. Upon patch formation, a paced response frequency of approximately 6 Hz was obtained, and decreased to approximately 3 Hz after 6 days of culture. High cell density patches contained a thicker real cardiac tissue layer, which generated higher R‐wave amplitudes; however, low‐density patches had a greater signal volume index of connexin 43. In addition, all patches manifested endothelial cell growth and robust nuclear division. The present study demonstrates that the proper time for in vivo implantation of this cardiac construct is just at patch formation, and patches with 3–4 M cell densities are the best candidates. Copyright © 2014 John Wiley & Sons, Ltd.